ФОРМИРОВАНИЯ УЧЕБНОЙ МОТИВАЦИИ СТУДЕНТОВ ТЕХНИЧЕСКИХ ВУЗОВ В ПРОЦЕССЕ ИЗУЧЕНИЯ ЕСТЕСТВЕННОНАУЧНЫХ ДИСЦИПЛИН - Мишенина, И.В.; Худоян, М.В.; Темираев, К.Б.; Шургаева, Е.В.; Хугаева, А.А. (SCIENCE and SOCIETY, 2024)
The article examines the formation of educational motivation of students of technical universities in the process of studying natural sciences. In modern educational psychology, the problem of motivation for educational activities is recognized as one of the most important. Motivation for educational activities is considered as the main factor in the successful achievement of the main goals of educational activities. Thus, the issue of educational motivation is essentially a matter of the quality of educational activities. The motives of educational activities largely determine the student’s attitude towards solving the professional tasks assigned to him and create the necessary conditions for the effectiveness of professional activities.